SURVIVAL OF YOUTHPRENEUR DURING PANDEMIC COVID19 - Nur Afrina Mohamad Aidil; Nur Hidayah Zainal (Journal of Islamic, Social, Economics and Development, 2022)
It is reported that the Small and Medium Enterprises (SMEs) contribution towards the nation economic growth has been declining 7.3% in the year 2020. Micro SME’S especially is coping with hard challenges as adapting businesses with the new norms requires not only money capital but also the required skills to sustain and survived. Despite the economic turbulence, added with the slow demand from the market and the impact of the unpredictable nationwide Movement Control Order (MCO), entrepreneurs need to ensure that the businesses are able to counter the shock. This study attempts to investigate the factors affecting the survival of youth entrepreneurs during pandemic Covid19, specifically the students whom businesses are categorized under the micro-SMEs. A quantitative study is conducted through online survey towards 389 youth entrepreneurs in Selangor using stratified sampling. The data is then analyzed using the descriptive analysis. Results showed that business plans, financial support and digital adoption in business marketing, operation and payment systems are the three major factors contributing to the survival of youth entrepreneurs during pandemic. Thus, adopting with the technology should be a great investment, plus acknowledging the financial supports that is provided to the micro-SMEs should sustained the youth entrepreneurs.